Diretrizes para implementação do planejamento de médio prazo: lições e desafios a partir de um projeto de construção de uma usina fotovoltaica de grande porte - Alves, Andreia Cardoso (2024)
Medium-Term Planning (PMP) is an LPS® planning horizon that promotes the interface between long-term planning and short-term planning. This is an approach that seeks to detail operations, identify and remove restrictions and create a bank of activities ready for execution. Through PMP, it is possible to protect production against problems related to projects, materials, equipment, labor, among others. However, despite its importance for construction management, PMP still faces difficulties in its implementation process, sometimes being executed in an ineffective way. Furthermore, there is a scarcity of studies related to PMP, in the context of infrastructure projects, despite the relevance of these projects for regional or national development. In this sense, there is a need to analyze PMP implementation process in infrastructure projects, with a view to identifying best practices and supporting construction professionals in carrying out this stage of LPS®. Thus, this research has as its starting point a set of conceptual and practical recommendations for implementation of PMP in construction projects. By analyzing the implementation of the PMP, in a construction project for a large photovoltaic plant, this research seeks to identify and discuss the difficulties in implementation and suggestions for improvements to the PMP used. The research strategy used was case study. The research was divided into three phases, namely: understanding, empirical study and reflection phases. In the understanding phase, the main approaches used to implement the PMP in construction projects were investigated. In the empirical study phase, the work explored the implementation of the PMP adopted in the photovoltaic plant, considering procedural, organizational and technical aspects. Research data collection occurred through interviews, document analysis and participant observation. During the empirical study phase, the research discussed planning indicators, perceived barriers to implementing the PMP and suggestions for relevant improvements. In the reflection phase, the work brought the main guidelines for the PMP, in photovoltaic plant projects, and presented a set of propositions for improving a medium-term conceptual model, taking into account literature findings and lessons learned, in empirical study. From the set of guidelines, it was concluded that the development of the restrictions notebook has the potential to help identify restrictions that prevent the beginning and continuity of activities, in addition to providing less dependence on the participants' memory. Furthermore, it was concluded that fostering collaboration, early participation of stakeholders, support from senior management, the use of risk analysis to prioritize restrictions, carrying out training, promoting visual management, daily monitoring of restrictions, among others, assist in the implementation of the PMP, providing guidance on the routines and implementation aspects that must be followed by photovoltaic plant projects.